Promoting urban development through smart planning - BOUALLAG-AZOUI , Ouafida (Journal of Human Sciences, 2022)
For twenty years, the term "Smart City" has become established in the discourse of professionals to designate a "connected" city product of the digital revolution and technological development. If this vision of urban intelligence highlights the evolution of research, it is reductive. The smart city is above all a social project that is based on both sustainability and the prevalence of the collective interest while ensuring the preservation of the environment and the renewal of resources. In this paper, we propose to focus on the main aspects that make it possible to promote the intelligence of the territory with the aim of identifying the positive interactions that can develop between technology and quality of urban space and that could be used to concretize the Algiers Smart City project that is slow to be realized.  Useful technologies are those that make it possible to increase the effectiveness and efficiency of the city's development levers while preserving the necessary balances.